PERANAN GURU PKn TERHADAP PEMBENTUKAN KARAKTER SISWA UNTUK MENINGKATKAN SIKAP NASIONALISME SISWA SMA NEGERI 1 PETIR KELAS XI IPS 2 KABUPATEN SERANG - E Nita Prianti; Anton Aulawi; Siti Khadijah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2019)
This research is aimed to investigate (1) role of Civics Education teachers in building students’ character through nationalism attitude. The research results show that the teachers’ role is highly needed because they are role models to make the students’ behavior and character better and beneficial in terms of life, so that students of SMA 1 Petir can improve their character of nationalism. (2) factors which influence the building of nationalism character (3) the teachers’ effort toward the students’ character building. Based on the results of the research, in their way to solve the problem, the teachers use PAIKEM method, where the learning teaches active, innovative, creative, and fun learning. The research method used in this study is descriptive analysis research with a qualitative approach. The source of data in this qualitative research is gotten by digging information /explanation directly from sources of information that are considered to be related to the building of students’ characters in XI IPS 2 of SMA 1 Petir. As for the informants, this research gets Civics Education teachers and students of SMA 1 Petir. Data collection techniques used by the researchers in this research are interviews, observations, and documentation. In addition, the data analysis technics used by the researchers in this qualitative research are data reduction, display, and verification.